2010
DOI: 10.1557/mrs2010.614
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Atomic Oxygen Reactions with Polymers and Combined Effects with Vacuum Ultraviolet Light

Abstract: This article focuses on mechanistic aspects of hyperthermal atomic oxygen reactions with polymers, which are the major contributor to material degradation in low Earth orbit. Due to the importance of well-controlled experiments in the understanding of the reaction mechanisms, ground-based experimental results obtained by a hyperthermal atomic oxygen beam generated by laser detonation facilities are mainly surveyed. Combined effects of atomic oxygen and vacuum ultraviolet (VUV) light on fluorinated polymers are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Supposedly, there are several steps involved in the AO exposure process for a polymer, including erosion initiation by O-surface interaction, erosion propagation by chain scission, and material loss due to volatile removal. 62 Among the three steps, the first two ones are dominated by chemical interactions and the last one by physical interaction such as atom collisions. ARPI-0 and Kapton HN have the similar element compositions.…”
Section: Resultsmentioning
confidence: 99%
“…Supposedly, there are several steps involved in the AO exposure process for a polymer, including erosion initiation by O-surface interaction, erosion propagation by chain scission, and material loss due to volatile removal. 62 Among the three steps, the first two ones are dominated by chemical interactions and the last one by physical interaction such as atom collisions. ARPI-0 and Kapton HN have the similar element compositions.…”
Section: Resultsmentioning
confidence: 99%
“…Literature reports are not fully conclusive on the synergistic effect of UV and AO, although it appears that for several polymers, such as polymethylmethacrylate (PMMA), polyethylene (PE), polyimide, and Teflon FEP, no particular synergy is discernible. 14,35 UV radiation is absorbed only in the top 1-3 mm of the specimen surface; hence, the polymer specimens subjected to UV radiation underwent surface degradation that created a $ 2 mm thick carpet layer at the top surface. 19 The degraded polymer retarded further degradation of the underlying polymer due to UV radiation.…”
Section: Resultsmentioning
confidence: 99%
“…13 Although the concentration of AO in LEO is small, the flux of AO impinging a spacecraft's outer surface is significant (10 14 -10 15 atoms/cm 2 ) due to the high orbital velocity (7-8 km/s) of the spacecraft. 14 Thus, AO impacting polymeric materials over extended periods of time will cause surface erosion and mass loss.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing Figures 2 (a), and (c), it is possible to observe that the front position was more heated active species are able to diffuse during liquid phase, and promote reactions, increasing the heating of the sample at the moment. At the same time, Tagawa 27,28 found that when polymers are exposed to atomic oxygen and UV light, the angle of incidence can increase the rate of interaction considerably. However, since the increase on the incident angle due the melt puddle of SA is minimal on experimental conditions, the effect of the presence of a liquid phase on SA is considerably more important to the heating.…”
Section: Experimental Measurements During Plasma Treatmentmentioning
confidence: 98%